Exploring the interrelationship of intra- and inter-network alteration in motor recovery after stroke - Jungsoo Lee; Yun-Hee Kim (Scientific Reports)
Abstract Brain networks demonstrate various dynamics during recovery after a stroke. Recovery of interhemispheric interaction and balance and the occurrence of network reorganization have also been reported during stroke recovery. This study aimed to investigate the dynamics of brain networks after stroke. At the large-scale brain network level, this study focuses on determining whether changes in brain networks during the functional recovery period following a stroke, along with concurrent changes in connected networks, facilitate functional recovery. Eighty-three subacute ischemic stroke patients participated. All patients underwent resting-state functional MRI and motor function assessments at two weeks and three months after stroke onset. Intra- and inter-networks from 12 resting-state networks were extracted from functional MRI data. The interrelationship between intra-network values changes and inter-network values between the corresponding network and other networks during the recovery period was investigated. The interrelationship between the good and poor recovery subgroups was compared. The interrelationship of intra- and inter-network alterations could be observed in both groups. This interrelationship was more pronounced across multiple networks in the good recovery group compared to the poor recovery group. The group differences in the interrelationship of intra- and inter-network alteration were shown in diverse sub-networks, including cognitive and sensory networks as well as motor networks. This study suggests the importance of adopting a plasticity-oriented perspective focused on changes in intra- and inter-network connectivity throughout the entire brain rather than solely emphasizing the motor function area for predicting and treating motor function recovery.